2006
DOI: 10.1124/jpet.106.106062
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene Elicits Combined Rapid Vasorelaxation and Long-Term Anti-Inflammatory Actions in Rat Aorta

Abstract: Previous studies reported the ability of raloxifene to acutely relax arterial and venous vessels, but the underlying mechanisms are controversial. Anti-inflammatory effects of the drug have been reported in nonvascular tissues. Therefore, the aim of this study was to investigate the nature of short-and longterm effects of raloxifene on selected aspects of vascular function in rat aorta. Isometric tension changes in response to raloxifene were recorded in aortic rings from ovariectomized female rats that underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Clinical and animal studies have suggested multiple benefits of SERM, and several SERMs have already been clinically approved, including raloxifene and tamoxifen. Recent findings have demonstrated the beneficial effects of these two classical SERMs upon the vascular system [52], [53], [54], [55]. Since raloxifene and tamoxifen share the same/similar antagonistic action with calycosin at ERβ, we compared the angiogenic effects of the three compounds in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and animal studies have suggested multiple benefits of SERM, and several SERMs have already been clinically approved, including raloxifene and tamoxifen. Recent findings have demonstrated the beneficial effects of these two classical SERMs upon the vascular system [52], [53], [54], [55]. Since raloxifene and tamoxifen share the same/similar antagonistic action with calycosin at ERβ, we compared the angiogenic effects of the three compounds in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
“…GPER is also expressed in non-endothelial vascular cells, such as smooth muscle cells (Haas et al, 2007; Isensee et al, 2009), being expressed in both human arteries and veins and being regulated in response to estrogen (Haas et al, 2007). Non-genomic vasodilator effects have been described for estrogen (a non-selective estrogen receptor agonist) and phytoestrogens (such as genestein) as well as antagonists of the “classical” estrogen receptors (ICI182,780) and SERMs (such as tamoxifen and raloxifene) (Leung et al, 2007; Meyer et al, 2009; Pinna et al, 2006). For many years, the relaxant effects of the latter remained unexplained mechanistically.…”
Section: Physiological Functions Of Gper As An Estrogen Receptormentioning
confidence: 99%
“…Similarly, raloxifene elicits rapid endothelium-dependent nitric oxide-mediated vasorelaxation in rat aorta that is not sensitive to either the nonselective ER antagonist ICI 182,780 or the selective ERα antagonist 1,3-bis (4-hydroxyphenyl)-4-methyl-5- (4-(2-piperidinylethoxy) phenol)-1H-pyrazole (MPP) [38]. Raloxifene also elicits long-term anti-inflammatory actions in rat aortic VSM cells via upregulation of ERα protein levels [39]. …”
Section: Modulators Of Vascular Ersmentioning
confidence: 99%